The route to financial sustainability of a large Public Private Partnership—the example of the clinical trial network conect4children (c4c) - Paumard, Laetitia; Hildebrand, Heidrun; Engel, Marianne; Lepola, Pirkko; Montero, Esther; Tennigkeit, Frank; Rosenmöller, Magda (Frontiers in Medicine, 2025)
BackgroundThe financial sustainability of publicly funded initiatives, particularly Public Private Partnerships (PPPs), is crucial for ensuring the intended long-term impact beyond the project’s funding phase. Despite many initiatives aspiring to lasting impact, very few practical examples and little evidence are available on successful financial sustainability strategies, and even fewer are available on the path to achieve the financial autonomy of any successor organisation. This paper intends to shed light on this aspect by exploring the strategy and challenges towards the financial sustainability of conect4children (c4c), an Innovative Medicines Initiative (IMI)-funded PPP establishing a pan-European paediatric clinical trial network to facilitate and support the planning and conduct of paediatric clinical trials.MethodsThe c4c project was planned for a lasting impact from the start. An entire work package dedicated to financial sustainability was already sketched in the proposal and started from the onset of the project, including benchmarking against clinical trial networks globally, needs assessment leading to a value proposition, service portfolio definition, analysis of legal requirements, and the development of a sound business concept.Resultsc4c adopted a combined approach, translating research findings into market-tested services through the parallel set-up of a standalone entity, c4c-Stichting (c4c-s). This strategy offers valuable insights into planning financial sustainability for similar large-scale initiatives and, more broadly, provides a significant contribution to the discourse on financial sustainability. These insights are highly relevant to Regulatory Science, as the sustainability of such infrastructures is critical to the success of regulatory science strategy and long-term public health outcomes.